ЖСТ МЕХАНИКАСЫНДАҒЫ ЖЫЛДАМДЫҚ КҮЙ ФУНКЦИЯСЫ РЕТІНДЕ - Abdildin, M.M.; Beiseen, N.A.; Boshkaev, K.A.; Taukenova, A.S. (Хабаршы. Физика сериясы, 2021)
In present work it is shown that representation of velocity as a function of state in GR mechanicstogether with improved Fock’s first approximation metrics and Euler’s hydrodynamic formula allows solve arelativistic rotational equation of motion unambiguity problem in GR mechanics.